1991
DOI: 10.1007/bf00226207
|View full text |Cite
|
Sign up to set email alerts
|

Stable transformation of Sorghum bicolor protoplasts with chimeric neomycin phosphotransferase II and β-glucuronidase genes

Abstract: Parameters influencing the stable transformation of Sorghum bicolor protoplasts with a chimeric neomycin phosphotransferase II (NPT II) gene by electroporation were investigated. The mean number of kanamycin-resistant calli produced increased in direct proportion to the concentration of DNA used for transformation. Linearization of the plasmid doubled the mean number of kanamycin-resistant calli produced, while the addition of carrier DNA had no effect. The copy number (1-4) of integrated genes was low compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…The first report of direct DNA uptake into protoplasts of sorghum by electroporation was carried out by Ou- Lee et al, (1986) and latter by Battraw and Hall (1991). Hagio et al, (1991) reported stable transformation from suspension cell cultures of Sorghum vulgare through microprojectile bombardment.…”
Section: Explants For Transformation and Plant Regenerationmentioning
confidence: 99%
See 4 more Smart Citations
“…The first report of direct DNA uptake into protoplasts of sorghum by electroporation was carried out by Ou- Lee et al, (1986) and latter by Battraw and Hall (1991). Hagio et al, (1991) reported stable transformation from suspension cell cultures of Sorghum vulgare through microprojectile bombardment.…”
Section: Explants For Transformation and Plant Regenerationmentioning
confidence: 99%
“…They include cat, npt II, hpt, bar and manA. Neomycin phosphotransferase II (npt II) gene isolated from E.coli conferring resistance to the antibiotic Kanamycin is one of the commonly used selection strategy for sorghum (Howe et al, 2006;Tadesse and Jacobs, 2004;Battraw and Hall, 1991). Hagio et al, (1991) reported the use of Hygromycin B phosphotransferase (hpt) as well as Neomycin phosphotransferase II (nptII) genes to confer Hygromycin and Kanamycin resistance, respectively.…”
Section: Role Of Selectable Markersmentioning
confidence: 99%
See 3 more Smart Citations